A pooled analysis of patients with wound infections in the Phase 3 REVIVE trials: randomized, double-blind studies to evaluate the safety and efficacy of iclaprim versus vancomycin for treatment of acute bacterial skin and skin structure infections. Issue 4 (20th March 2020) - Noviello, Stephanie; Corey, G. Ralph; Holland, Thomas L.; Lodise, Thomas; O'Riordan, William; Wilcox, Mark H.; File, Thomas M.; Dryden, Matthew; Balser, Barbara; Scaramucci, Amy; Torres, Antoni; Huang, David B.
Abstract : Introduction. Iclaprim is a diaminopyrimidine antibiotic for the treatment of acute bacterial skin and skin structure infections (ABSSSI) due to Gram-positive pathogens. Aim. This analysis evaluates patients with wound infections from two Phase 3 trials of ABSSSI. Methodology. Six-hundred-two patients with wound infections from two Phase 3, double-blinded, randomized, multicenter, active controlled trials (REVIVE-1/–2) were evaluated in a post hoc analysis of iclaprim 80 mg compared with vancomycin 15 mg kg –1 administered intravenously every 12 h for 5–14 days. The primary endpoint was to determine whether iclaprim was non-inferior (10 % margin) to vancomycin in achieving a ≥20 % reduction from baseline in lesion size 48–72 h after starting study drug (early clinical response [ECR]). Safety was assessed. Results. In REVIVE-1, ECR was 83.5 % with iclaprim versus 79.7 % with vancomycin (treatment difference 3.77%, 95 % CI −4.50%, 12.04%). In REVIVE-2, ECR was 82.7 % with iclaprim versus 76.3 % with vancomycin (treatment difference 6.38%, 95 % CI −3.35%, 16.12%). In the pooled dataset, iclaprim had similar ECR rates compared with vancomycin among wound infection patients (83.2 % vs 78.2 %) with a treatment difference of 5.01 % (95 % CI −1.29%, 11.32%). The safety profile was similar in iclaprim- and vancomycin-treated patients, except for a higher incidence of diarrhea with vancomycin ( n =17) compared with iclaprim ( n =6) and fatigue with iclaprim ( n =17) compared with vancomycin ( n =8). Conclusion. Based on early clinical response, iclaprim achieved non-inferiority to vancomycin with a similar safety profile in patients with wound infections suspected or confirmed as caused by Gram-positive pathogens. Iclaprim may be a valuable treatment option for wound infections.